2010
DOI: 10.1007/s00595-009-4010-0
|View full text |Cite
|
Sign up to set email alerts
|

Intersigmoid hernia: Report of a case

Abstract: A 28-year-old man with no previous history of abdominal surgery presented at a local hospital with abdominal pain. He was diagnosed to have an intestinal obstruction and was treated conservatively. However, the symptoms persisted, and he was thereafter referred to this hospital. Plain abdominal radiographs demonstrated small-bowel gas. A computed tomographic scan of the abdomen disclosed wall thickening of an edematous, fluid-filled ileum. An exploratory laparotomy was performed to determine the cause of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 7 publications
(9 reference statements)
1
27
1
Order By: Relevance
“…Indeed, previous attempts at nonoperative management of incarcerated intersigmoid hernias have been unsuccessful. 1,2 In these previously reported cases, laparotomy was eventually required and the length of stay was 8 days, compared with 36 hours after the laparoscopic repair in the present case.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Indeed, previous attempts at nonoperative management of incarcerated intersigmoid hernias have been unsuccessful. 1,2 In these previously reported cases, laparotomy was eventually required and the length of stay was 8 days, compared with 36 hours after the laparoscopic repair in the present case.…”
Section: Discussionmentioning
confidence: 45%
“…Although historically an intersigmoid hernia was thought to be most common subtype, 4 a recent literature review suggests that intramesosigmoid hernia is the most common. 1 Internal hernias are the cause of small intestinal obstruction in less than 4% of cases. 2 The incidence is much higher, however, after gastric bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of bowel resection is higher in those patients with transmesosigmoid hernia (50%) than in those with intersigmoid hernia (18.8%) or intramesosigmoid hernia (13.9%) because the herniated loop of the bowel is often long and easily causes strangulation, leading to intestinal necrosis [5]. In contrast, in patients with intersigmoid hernia, the incarcerated loop is very short as the sigmoid fossa only builds a small cavity; therefore, circulatory disturbance seldom occurs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of intersigmoid hernia, the space of the intersigmoid fossa is not very large - from a mere dimple to a size that will admit the whole index finger -, with the possibility of contained bowels in the fossa being limited, and therefore detection of the incarcerated bowel is difficult. Nihon-Yanagi et al [5] reported a case of intersigmoid hernia. In their patient, CT could disclose an enlarged fluid-filled ileum with an edematous wall in the left iliac fossa and pelvic cavity.…”
Section: Discussionmentioning
confidence: 99%